Surfacing in the Ecofeminist Classroom - Dickson Bruckner, Lynne (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
After an overview of current debates in ecofeminist theory, this essay demonstrates how Atwood's Surfacing is a central text in the ecofeminist classroom. Published in 1972, Atwood's novel anticipates many contemporary debates in ecofeminism. Surfacing underscores the damaging impact of patriarchal structures, while also assigning responsibility for environmental degradation to men and women both.